Analysis of the differences and influencing factors of rural population aging in Gansu Province—based on panel data from 2000 to 2022 - Liu, Yue; Lv, Fengli; Zhang, Xiaochen; Wang, Jiancheng (Frontiers in Public Health, 2025)
ObjectiveTo analyze the spatial dimension differences and influencing factors of rural population aging in Gansu Province over the past 20 years.MethodsData on population, economy, healthcare, and education from Gansu Province and its 14 cities (prefectures) from 2000 to 2022 were collected, with selected indicators quantified. A spatial dynamic panel data model was established to explore regional differences and the impact of influencing factors on population aging.ResultsThe aging of the rural population in Gansu Province continues to intensify, with regional disparities gradually widening. Among these, the central region exhibits the largest disparity and contribution rate, followed by the southeastern region, while the northwestern region shows the smallest. Intra-regional disparities, particularly in the central region, are the primary source of the overall disparities. Among the influencing factors, an increase in population density helps alleviate aging, whereas a rise in the illiteracy rate exacerbates population aging. Other factors, including the natural population growth rate, GDP per capita, and the number of hospital beds per capita, do not have a significant impact on population aging.ConclusionThe aging of the rural population in Gansu is intensifying, with regional disparities widening, influenced by multiple factors such as economic development, population growth, education levels, and medical resources.